2012 IEEE 25th International Conference on Micro Electro Mechanical Systems (MEMS) 2012
DOI: 10.1109/memsys.2012.6170394
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-level integrated electrospray emitters for a pumpless microthruster system operating in high efficiency ion-mode

Abstract: Microfabrication, wafer-level integration, and characterization of internally fed arrays of electrospray thrusters for spacecraft propulsion are discussed. 5 µm inner diameter, 100 µm long capillaries and 150-to-300 µm diameter annular extractor electrodes are integrated vertically via a polymer based wafer bonding process, allowing high yield and post testing disassembly of the bonded stack. The small inner diameter of the capillaries allows passive, capillary force driven delivery of the propellant to the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…After characterizing the ToF system and the ion guide for needle emitters, the system was used for spray characterization of capillary-fed internally wetted microfabricated emitters, such as the one shown in [32,55] (see Supplementary Figure S3 for SEM image). A microfabricated reservoir, created just beneath the capillary emitter, is first filled with ionic liquid and the liquid then reaches the tip of the emitter by capillary process.…”
Section: Experimental Results Using Microfabricated Capillary Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…After characterizing the ToF system and the ion guide for needle emitters, the system was used for spray characterization of capillary-fed internally wetted microfabricated emitters, such as the one shown in [32,55] (see Supplementary Figure S3 for SEM image). A microfabricated reservoir, created just beneath the capillary emitter, is first filled with ionic liquid and the liquid then reaches the tip of the emitter by capillary process.…”
Section: Experimental Results Using Microfabricated Capillary Emittersmentioning
confidence: 99%
“…The extraction voltage is then applied. We have previously observed that these devices emit currents of up ±2 μA [35,55], in mixed iondroplet mode with emission half-angle of 40° [32] at operating voltages between ±700 V and 1000 V. Retarding potential analysis (RPA) of these devices has previously shown that the kinetic energy of emission can have nearly 10% deficit from the applied emitter potential V em [35,36]. There can also be secondary peaks [35,36] corresponding to ion defragmentation in which dimers can break into neutral molecules and a monomers during their flight and share the kinetic energy according to the ratio of their masses.…”
Section: Experimental Results Using Microfabricated Capillary Emittersmentioning
confidence: 99%
“…Previous thruster prototypes produced by our group were comprised of microfabricated arrays of 19 bead-filled capillary emitters [13,14] with a single extraction stage. Our latest generation uses a simpler, improved emitter fabrication process and wafer-level bonding of the electrodes, which we had proposed earlier [15]. The new process permits the large scale fabrication of high aspect ratio capillaries with the smallest <10 µm inner diameters to date.…”
Section: Introductionmentioning
confidence: 99%
“…Our latest generation uses a simpler, improved emitter fabrication process and wafer-level bonding of the electrodes, which we had proposed earlier [15]. The new process permits the large scale fabrication of high aspect ratio capillaries with the smallest <10 µm inner diameters to date.…”
mentioning
confidence: 99%